Biomass Organic Rankine Cycle for an industrial application - Ungureșan Paula Veronica; Pleșa Angela; Tărnar Gabriel; Bian Mihaela (E3S Web of Conferences)
The article presents a technical approach aimed at improving the energy efficiency of a furniture manufacturer. The proposed solution involves supplying the furniture factory with heat and electricity by integrating the existing biomass boiler with an Organic Rankine Cycle. An assessment was conducted on four distinct working fluids: D5, MD4M, m-Xylene, and Toluene. The results suggest that toluene yields the highest electrical efficiency